AN ANALYSIS OF ENGLISH PHRASAL VERB IN ABANDON NOVEL AND ITS TRANSLATION - Wulandari, Ratna (Universitas Gunadarma, 2015)
The researcher conducts a research with the topic An Analysis of English Phrasal Verb in The Novel “Abandon” and its translation. Through this research, the researcher finds out English Phrasal Verb in novel that has been translated into Indonesian. In this research, the writer focused on what kind of English phrasal verbs that occur in the Abandon novel and the meanings its translation. The purposes of this research are to find out the difficulties encountered by the researcher in the translation of English phrasal verb and to solve the difficulties faced by the researcher in translating English phrasal verb in the Abandon Novel by Meg Cabot. This research employs descriptive qualitative research. The data of this research are some of the phrasal verbs Taken from Cabot’s Abandon, and its translation by Lucia Aryani. From the novel, the researcher only took thirty sentences which contain English phrasal verb randomly from first 65 pages of the novel. The result of the study shown that from 30 data, 21 data belong to level shift that consists of phrasal verb into verb and The researcher find 9 data belong to equivalence translation that consists of formal equivalence and dynamic equivalence. Keywords: Phrasal verb, Translation, Equivalence, Shift